2013
DOI: 10.1091/mbc.e12-09-0679
|View full text |Cite
|
Sign up to set email alerts
|

ZYX-1, the unique zyxin protein ofCaenorhabditis elegans, is involved in dystrophin-dependent muscle degeneration

Abstract: The LIM-domain protein ZYX-1 is the unique zyxin-like protein in Caenorhabditis elegans. In striated body-wall muscles, ZYX-1 localizes at dense bodies/Z-discs and M-lines, as well as in the nucleus, and its localization is highly dynamic. ZYX-1 plays an unexpected role in dystrophin-dependent muscle degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 103 publications
(103 reference statements)
3
52
1
Order By: Relevance
“…Prior work in C. elegans has examined the role of zyx-1 in muscle (Lecroisey et al, 2008(Lecroisey et al, , 2013. As mentioned earlier, ZYX-1 is localized to dense bodies in muscle and this localization is ATN-1 dependent.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Prior work in C. elegans has examined the role of zyx-1 in muscle (Lecroisey et al, 2008(Lecroisey et al, , 2013. As mentioned earlier, ZYX-1 is localized to dense bodies in muscle and this localization is ATN-1 dependent.…”
Section: Discussionmentioning
confidence: 91%
“…Zyxin has been demonstrated to interact with focal adhesions via α-actinin (Reinhard et al, 1999). Furthermore, prior studies revealed that zyx-1 muscle phenotypes (in a dys-1 hlh-1 mutant background) are mediated via the worm α-actinin ATN-1 (Lecroisey et al, 2013). However, atn-1 mutants formed PLM synapses normally ( Table 1), indicating that ZYX-1 functions via different interacting proteins in muscle versus PLM neurons.…”
Section: Developmental Studies Confirm Synaptic Lossmentioning
confidence: 98%
See 2 more Smart Citations
“…Strains that overexpress a given transgene are useful tools to study i) the subcellular localization of proteins, which exhibit a low endogenous expression level, ii) the effect of the overexpression of a protein on worm physiology, or iii) the effect of the overexpression of a protein in a particular tissue 11 . Several applications require however the use of low or single copy integrated transgenes that can be generated with alternative methods such as coinjection of the transgene of interest along with single stranded oligos 2 , bombardment 12 , Mos1 transposon mediated Single Copy gene Insertion (MosSCI) 13 or Cas-9-triggered homologous recombination 14 .…”
Section: Discussionmentioning
confidence: 99%